PENGARUH UMP DAN LUAS LAHAN TERHADAP PENYERAPAN TENAGA KERJA SEKTOR PERTANIAN DI PROVINSI INDONESIA - Devi Andriyani; Aznuriliana Aznuriliana (LPPM Universitas Malikussaleh - Indonesia, 2022)
This study aims to analyze the effect of the provincial minimum wage (UMP) and land area on the Absorption of Labor in the Agricultural Sector in Indonesian Provinces. The research was conducted in 34 provinces from 2015 to 2020. The analytical method used is the fixed effect panel data regression analysis. The results showed that partially the UMP had no effect on employment, while the area of agricultural land had an effect on employment absorption, while simultaneously the UMP and land area had had an effect on employment in Indonesian provinces. West Java Province is the province with the largest intercept value, this means that changes in UMP and land area greatly affect employment in West Java. While overall, the magnitude of the influence of UMP variables and land area on employment absorption in Indonesia is 95.29%.